2012
DOI: 10.1161/atvbaha.111.238899
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 4 Mediates Monocyte Priming and Accelerated Chemotaxis Induced by Metabolic Stress

Abstract: Objective Metabolic disorders increase MCP-1-induced monocyte chemotaxis in mice. The goal of this study was to determine the molecular mechanisms responsible for the enhanced responsiveness of monocytes to chemoattractants induced by metabolic stress. Methods and Results Chronic exposure of monocytes to diabetic conditions induced by human low-density lipoproteins plus high D-glucose concentrations (LDL+HG) promoted Nox4 expression, increased intracellular H2O2 formation, stimulated protein S-glutathionylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
133
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(143 citation statements)
references
References 62 publications
8
133
0
Order By: Relevance
“…We showed that in mice the chemotactic activity of monocytes increases with rising levels of hyperglycemia and hyperlipidemia and is associated with increased macrophage recruitment and accelerated atherosclerotic lesion formation (18). We further demonstrated that metabolic stress induces the expression of Nox4, an inducible Nox family member that we identified in monocytes and macrophages (19) and which plays a critical role in monocyte priming by metabolic stress (17). The aim of this study was to elucidate the mechanisms underlying the conversion of monocytes into this hypermigratory, proatherogenic phenotype induced by metabolic stress and to identify the redoxsensitive pathways targeted by Nox4-derived ROS in primed monocytes.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…We showed that in mice the chemotactic activity of monocytes increases with rising levels of hyperglycemia and hyperlipidemia and is associated with increased macrophage recruitment and accelerated atherosclerotic lesion formation (18). We further demonstrated that metabolic stress induces the expression of Nox4, an inducible Nox family member that we identified in monocytes and macrophages (19) and which plays a critical role in monocyte priming by metabolic stress (17). The aim of this study was to elucidate the mechanisms underlying the conversion of monocytes into this hypermigratory, proatherogenic phenotype induced by metabolic stress and to identify the redoxsensitive pathways targeted by Nox4-derived ROS in primed monocytes.…”
Section: Discussionmentioning
confidence: 64%
“…MKPs are sensitive to inactivation via the reversible oxidation of their active-site cysteine (32). We showed that in monocytes metabolic stress promotes protein S-glutathionylation, i.e., the formation of mixed disulfides between GSH and reactive protein thiols (17,18); however, Sglutathionylation of MKPs had not been reported. To identify the mechanism by which metabolic stress promotes the inactivation and loss of MKP-1 in monocytes and to explore whether MKP-1 is S-glutathionylated in metabolically primed monocytes, we preloaded THP-1 monocytes with biotin-labeled glutathione and performed streptavidin-bead pulldown experiments.…”
Section: Metabolic Stress Promotes S-glutathionylation and Subsequentmentioning
confidence: 91%
See 3 more Smart Citations